Neotype designation and redescription of Gloydius shedaoensis qianshanensis Li, 1999 (Squamata, Serpentes, Viperidae) - Qiu, Xian-Chun; Wang, Xiao-Ping; Qi, Shuo; Wang, Jin-Ze; Xia, Zu-Yao; Wang, Hao-Tian; Zhou, Sheng-Bo; Yu, Guo-Xu; Wu, Zhong-Xun; Shi, Jing-Song; Li, Pi-Peng (Herpetozoa (Wien), 2023)
The taxonomic status of Gloydius shedaoensis qianshanensis Li, 1999 has long been debated due to its narrow distribution range, low population, loss of type specimens, and lack of detailed descriptions. Neotypes were designated based on newly collected specimens in the Qianshan Mountain area, detailed comparisons between G. s. shedaoensis , and G. s. qianshanensis were recorded, while we redescribed G. s. qianshanensis . PCA results based on the external morphology of the two subspecies of G. shedaoensis demonstrate the inter-population distinction of G. s. shedaoensis and G. s. qianshanensis , including head length, and dorsoventral-postorbital stripe width. Additionally, the ecological data of G. s. qianshanensis were recorded as supplements while providing further conservation strategies.